Analysis and Research on Poor Shunting of Track Circuits in High-speed Railway Stations Based on Computer Technology. Issue 4 (October 2020) - Zhang, Zhiguo; Shi, Mengxin; Wang, Ruyu
Abstract: Poor shunting of track circuit in high-speed railway station is a common problem, which has puzzled the traffic and electrical departments for many years. 25 Hz phase sensitive track circuit is the main part of electrified section in the station, while 480 track circuit is the main part of non electrified section. At present, the inspection of train occupation caused by the poor shunting of track circuit in high-speed railway station has become a major safety problem. Through continuous statistics and analysis, circuit experts have analyzed the causes of poor shunting of internal track circuit. Through the continuous research on the bad track circuit shunting, the high-speed railway has taken some measures to reduce the bad condition of the entry, such as adjusting the transmission voltage of the existing track circuit or using the electronic high-voltage pulse track circuit. However, we have yet to find a safe, reliable and economic programme. Therefore, this paper first uses computer technology to analyse the principle of bad circuit shunt. Then, this paper lists some classifications. Finally, this paper puts forward some solutions.